Faktor Penentu Keberhasilan Pasar Fashion Tradisional - Yen Efawati (Jurnal Riset Bisnis dan Investasi, 2016)
The purpose of this study to reveal the opinions of visitors or potential buyers of fashion at traditional markets are located in PasarBaru Trade Center, Bandung. The population is all visitors in one day with the criteria you have shopped over three times a month and the age of an adult. This research uses a descriptive method with purposive sampling technique, with an average analysis.The findings show that the products offered, locations, promotions, the services provided by merchant included in the criteria fairly well. The advantages of fashion PasarBaru Trade Center only includes lower prices and compete. Meanwhile, weakness of the infrastructure is minimal. The implication for retailers is that they need to sell more quality products, fashion is full of innovation, conduct joint promotions shows honest behavior in business.